Knowledge and Attitude about Health Reproduction among Female Adolescents using The SKATA-BKKBN Instrument - Monica Kartini; Masruchi Masruchi (Jurnal Kesehatan, 2021)
Adolescents is a vulnerable group and face various challenges, especially in the area of sexual and reproductive health (SRH). The problem that is often faced by adolescents is lack of understanding about developments that occur, as well as how to respond to these developments. This study aims to determine the level of knowledge and attitude regarding reproductive health among female adolescents living in rural areas using the SKATA instrument from the BKKBN. This study is a non-experimental study with a cross-sectional approach. The research subjects were 42 female adolescents aged 10-20 years with total sampling technique. The questionnaire to determine the subject's knowledge of reproductive health used the SKATA instrument compiled by the BKKBN. Data were analyzed using univariate analysis and bivariate analysis with Chi-square. The respondents’ level of knowledge about reproductive health was mostly in the poor category (71.4%), while the adequate level of knowledge was as many as 7 people (16.7%) and the level of good knowledge was 5 adolescents (11, 9%). Most of the respondents had sufficient attitudes regarding reproductive health (59.5%), while 11 people (26.2%) had poor attitudes, and 6 adolescents (14.3%) had good attitudes towards reproductive health. There was no significant correlation between respondents' knowledge and attitudes about reproductive health (p=0.341). The level of knowledge of respondents about reproductive health was mostly inadequate, and the attitudes of the respondents were mostly in the sufficient category. Innovative efforts are needed to be able to reach the adolescents and their families to increase their understanding and attitudes about reproductive health.